Prevalence of HPV infection in hypopharyngeal and laryngeal squamous cell carcinoma at Thailand's largest tertiary referral center - Warut Pongsapich (2018)
© 2017 The Author(s). Background: Following the well-established relationship between human papillomavirus (HPV) and cervical carcinoma, the carcinogenicity of this virus has also been confirmed in subsets of head and neck carcinoma (HNCA), but mainly in the oropharynx. Other subsites of HNCA with less known association to HPV have never been studied in Thailand. Accordingly, the aim of this study was to investigate the prevalence of HPV DNA in hypopharyngeal and laryngeal squamous cell carcinoma in Thai population. Methods: This cross-sectional study included hypopharyngeal and laryngeal squamous cell carcinoma patients diagnosed and treated at the Department of Otorhinolaryngology, Siriraj Hospital during the September 2011-December 2013 study period. Presence of HPV genome was confirmed by polymerase chain reaction from pathologically-confirmed fresh specimens. Demographic data and risk factors of HPV infection were evaluated. Results: Eighty patients were included, and 95% of those were male. Only one patient was noted with positive HPV-62 serotype. Most patients consumed tobacco and/or alcohol. Five patients had no risk factors for cancer development. Risk of HPV infection was evaluated by self-reporting questionnaire. The mean age of sexual debut was 20.17 years. Forty-eight patients had multiple sexual partners. Sixteen and seven patients had history of sexually transmitted disease infection and habitual oral sex contact, respectively. Conclusion: There was no oncogenic HPV DNA detected within pathologic specimens of laryngeal and hypopharyngeal cancers in this study. Compared to rates reported from developed countries, the prevalence of HPV-related HNCA in Thailand is very low.